A Novel Secure Web Usage Mining Technique to Predict Consumer Behaviour (NSWUM-PCB) - Sonia Sharma, Dalip (International Journal of Advanced Science and Technology, 2020)
Nowadays, World Wide Web has become a popular medium to search information, business, trading and so on. Various organizations and companies are also employing the web in order to introduce their products or services around the world. The important task is to know the behaviour of consumer visiting their site regularly and also the security of data collected at web server on daily basis.Since the data is useful to extract the information and knowledge of the visiting consumer. In the Internet age, the term data integrity is tightly connected to servers and databases, since this is where most of the world’s information is stored.and the threat of tempering with original data arises. In the past, many data mining techniques have developed to know the interest of the consumer visiting the site but those techniques not gives the assurance of security of data.  In this paper a novel secure web usage mining technique to predict consumer behaviour (NSWU-MPCB) is produced and its implementation on real time data is shown that not only provide security of data and also predict the consumer behavior with web usage mining in a very fast and efficient way. Keywords: Web Usage Mining, Data Integrity, Security.